Use of surgical task shifting to scale up essential surgical services: a feasibility analysis at facility level in Uganda - Galukande, Moses; Kaggwa, Sam; Sekimpi, Patrick; Kakaire, Othman; Katamba, Achilles; Munabi, Ian; Mwesigye Runumi, Francis; Hagopian, Amy; Blair, Geoffrey; Barnhart, Scott; Luboga, Sam; Mills, Ed. (MC health services research, 2013)
The shortage and mal-distribution of surgical specialists in sub-Saharan African countries is born out of shortage of individuals choosing a surgical career, limited training capacity, inadequate remuneration, and reluctance on the part of professionals to work in rural and remote areas, among other reasons. This study set out to assess the views of clinicians and managers on the use of task shifting as an effective way of alleviating shortages of skilled personnel at a facility level. Methods: 37 in-depth interviews with key informants and 24 focus group discussions were held to collect qualitative data, with a total of 80 healthcare managers and frontline health workers at 24 sites in 15 districts. Quantitative and descriptive facility data were also collected, including operating room log sheets to identify the most commonly conducted operations. Results: Most health facility managers and health workers supported surgical task shifting and some health workers practiced it. The practice is primarily driven by a shortage of human resources for health. Personnel expressed reluctance to engage in surgical task shifting in the absence of a regulatory mechanism or guiding policy. Those in favor of surgical task shifting regarded it as a potential solution to the lack of skilled personnel. Those who opposed it saw it as an approach that could reduce the quality of care and weaken the health system in the long term by opening it to unregulated practice and abuse of privilege. There were enough patient numbers and basic infrastructure to support training across all facilities for surgical task shifting.
Keywords: Surgical; Task shifting; ,Uganda; Human Resource for Health crisis